Forensic Audit In Dislosure Of Fraud Financial Reports : Literature Study - Cici (PT. Inovasi Teknologi Komputer, 2024)
The aim of this research is to find out the basics of fraud in the company environment. This research process was carried out observationally and exploratively using literature review techniques which aim to systematically examine forensic audits to identify fraud. For this purpose, digital literacy is achieved using electronic databases. The scope of this research includes all research papers and studies related to the field of forensic auditing for fraud detection. Sample selection was carried out in several steps. First, it is necessary to observe and analyze various sources of information related to the research. Second, by collecting and applying literature portfolio methods that are appropriate and relevant to similar research topics in the form of academic works in the form of journals, essays, news, books or other sources, digital is about promoting literacy. The research results are that economic actors must not cheat or manipulate financial reports, and company accountants must strictly comply with ethical principles and standards. If a company's finances are not good, the first step to take is to disclose it to interested parties because if they manipulate it, it will cause big losses and harm many people.